2017
DOI: 10.1177/1043463117734179
|View full text |Cite
|
Sign up to set email alerts
|

Status, identity, and ability in the formation of trust

Abstract: The sources of trust-or actor A's belief about actor B's trustworthiness with respect to particular matter Y-are myriad, ranging from the biological to the political. Despite the great amount of research that has investigated decision making as a function of another's ascribed and achieved characteristics, we still know little about whether and to what extent these characteristics impact A's trust in B regarding matter Y. In this article, I draw on classic sociological traditions-status characteristics theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 132 publications
0
23
0
Order By: Relevance
“…These are important to explore not only for the present research but also for research that has or will use designs of similar complexity (e.g. Matsueda et al, 2016;Robbins, 2016aRobbins, , 2016bRobbins, , 2017.…”
Section: Methods Effects In Survey Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are important to explore not only for the present research but also for research that has or will use designs of similar complexity (e.g. Matsueda et al, 2016;Robbins, 2016aRobbins, , 2016bRobbins, , 2017.…”
Section: Methods Effects In Survey Experimentsmentioning
confidence: 99%
“…Our goals were threefold then: first, contribute novel findings to the methods literature on survey experiments; second, explore whether and to what extent features of a survey experiment's design bias findings, especially in relation to prior and future work (e.g. Bansak et al, 2016;Hainmueller and Hopkins, 2015;Matsueda et al, 2016;Robbins, 2016aRobbins, , 2016bRobbins, , 2017; and third, modify elements of our design for future applications and replications.…”
Section: Methodological Implicationsmentioning
confidence: 99%
“…Yet, during team interactions, an implicit hierarchy will emerge since relevant expertise generates a deeper understanding of the task and higher expectations from others (Bunderson & Boumgarden, 2010). Experts then possess fairly high status in this hierarchy (Bunderson et al, 2016; Robbins, 2017).…”
Section: Literature Review and Model Constructionmentioning
confidence: 99%
“…Despite resolving the oversimplification of team creativity in the random variation model and recognizing the necessity of exploring team creative process, the creative synthesis model neglects the reality that however complex a task is, there are always a few individuals playing a leading role in a team (Bock, 2015). These individuals do not always contribute to the highest level of individual creativity, but are often provided with rich task‐related knowledge and experience, that is, expertise (Weisberg, 2006), and are therefore titled “experts.” Although expertise has been consistently overlooked in research on team creativity (Campbell, 1960; Simonton, 1999), creativity calling for thinking outside the “lines” seems exactly opposite to expertise that represents the “lines.” However, the prominent role of individuals with specific expertise in teamwork implies expertise brings not merely an automatic mode for information processing, but a highly complex conceptual structure for the representation and reasoning of the task situation (Bunderson, Van Der Vegt, Cantimur, & Rink, 2016; Dippong & Kalkhoff, 2015; Robbins, 2017; Weisberg, 2006), and the creative association between unrelated knowledge units (Neisser, 1976; Weisberg & Hass, 2007). Experts are thus adept at generating new ideas, judging the value of new ideas, and promoting the continuous improvement and implementation of the best ones among them.…”
mentioning
confidence: 99%
“…Interestingly, social factors are also able to influence men's and women's cooperation. Number of studies suggested that social characteristics, for example, social status (Robbins, 2017), identity (Simpson, 2006), social distance between subjects (Becchetti et al, 2011) influenced decision-making and trust. It is known that humans being "social animals" aspire to connect with each other because their survival depends on the group, on common goals and interaction (Aronson, 1972;Bowlby, 1969).…”
Section: Introductionmentioning
confidence: 99%